Effect of Deformation Structure of AISI 316L in Low-Temperature Vacuum Carburizing - Hyunseok Cheon (MDPI AG, 2021)
The effect of plastic deformation applied to AISI 316L in low-temperature vacuum carburizing without surface activation was investigated. To create a difference in the deformation states of each specimen, solution and stress-relieving heat treatment were performed using plastically deformed AISI 316L, and the deformation structure and the carburized layer were observed with EBSD and OM. The change in lattice parameter was confirmed with XRD, and the natural oxide layers were analyzed through TEM and XPS. In this study, the carburized layer on the deformed AISI 316L was the thinnest and the dissolved carbon content of the layer was the lowest. The thickness and composition of the natural oxide layer on the surface were changed due to the deformed structure. The natural oxide layer on the deformed AISI 316L was the thickest, and the layer was formed with a bi-layer structure consisting of an upper Cr-rich layer and a lower Fe-rich layer. The thick and Cr-rich oxide layer was difficult to decompose due to the requirement for lower oxygen partial pressure. In conclusion, the oxide layer is the most influential factor, and its thickness and composition may determine carburizing efficiency in low-temperature vacuum carburizing without surface activation.